Effect of fatigue cracks in the wall on the strength of crane beams - G. I. Belyy; A. E. Kubasevich (Vestnik MGSU)
Introduction. In industrial plants with overhead cranes of heavy and very heavy modes of operation, crane beams are operated with damage, a significant part of which are fatigue cracks in the wall. At the same time, in many cases, damaged crane beams have reserves of bearing capacity, which, at the initial stage of crack development, allow their temporary operation until repair or replacement. Assessment of the effect of fatigue cracks on the strength of crane beams under these conditions becomes actual.Materials and methods. To study the stress-strain and limit states of crane beams with fatigue cracks in the wall, the method of numerical modelling using the finite element software complex ANSYS is used. The analysis of the stress-strain states of the beams was carried out in the sections corresponding to the crack centre and in the adjacent to the damaged compartments.Results. Qualitative and quantitative dependences of changes in the stress-strain and limit states of crane beams on the crack length, its position in the compartment under separate action of bending moment and transverse force, as well as their joint action are revealed. It is shown that the weakening of the wall by a fatigue crack leads to significant overload of the compressed girdle. Recommendations on inhibition of crack development, allowing to increase serviceability of the structure.Conclusions. Recommendations on practical calculation of crane beams for strength with the introduction of crack influence coefficients and an algorithm for determining the maximum crack length are proposed. The importance of further investigation of the effect of defects of rail to girdle fastening on the bearing capacity of the damaged beam is noted. At the same time, statistical processing of deviation values of geometric imperfections acquired in the course of operation is necessary.